Loss of length of the dental arch in children aged 8 to 11 - Liuba González Espangler; Yumeidis Ramírez Quevedo; Wuilfrido Eredis Durán Vázquez; Javier Melchor Moreno Brooks (Centro Provincial de Información de Ciencias Médicas, 2016)
A descriptive, observational and cross-sectional study of 332 children aged 8 to 11 with non physiologic loss of the dental arch, assisted in "José Martí Pérez" Teaching Polyclinic Stomatological Clinic in Santiago de Cuba was carried out from September, 2014 to December, 2015, in order to describe the predisposing factors to this disorder.  The patients were examined with the help of the natural light, slide gauge and a lingual depressor, and the calculated averages of the upper and lower dental arches length were 31 mm and 29 mm, respectively, with a higher implication in the 11 years children.  In the evaluated population the males prevailed, the mostly found predisposing factor was the interproximal decay and the higher mean length values were in the upper arch and in the right hemiarches.